Reality as a construct: outline of a pragmatic constructivist perspective - Nørreklit, Lennart (Proceedings of Pragmatic Constructivism, 2014)
Consider the idea that reality is a construct. Are constructivist and realist perspectives not incompatible? Well, they are often construed as more or less incompatible and competing perspectives: Constructivism being mainly considered a subjectivist and idealistic perspective while the opposite perspective, realism, is considered an objectivist or materialist perspective. However, the ordinary usage of the terms ‘reality’ and ‘construction’ discloses no contradiction but a group of nicely interrelated concepts.